PEMBERDAYAAN KELOMPOK TANI DALAM PENGELOLAAN LAHAN PADI PASANG SURUT MELALUI PENGATURAN TATA AIR SISTEM BERTINGKAT DAN APLIKASI BIOMASSA IN SITU - Ichriani, G.I.; Razie, F. (Buletin Udayana Mengabdi; Vol 23 No 4 (2024): Buletin Udayana MengabdiDO - 10.24843/BUM.2024.v23.i04.p13, 2023)
Farmers in Sawahan Village, Cerbon District, Barito Kuala Regency, South Kalimantan do not yet have the knowledge and skills to manage tidal rice fields, which are constrained by acidity and high soluble iron content, low fertility, and flooding throughout the year or periodically. Water management system technology and biomass applications can overcome these problems so as to increase the productivity of rice fields. Application of tidal swamp-specific technology was able to increase Ciherang and Inpara 2 rice production, namely 4.34 t GKG/ha and 7.3 t GKG/ha, respectively. The objectives of the community service activities carried out with the partners of the Suka Maju Farmers Group are: (1) introducing tidal swamp water management technology and soil repairing biomass; (2) increasing the knowledge and skills of site-specific land management techniques for rice farmers; and (3) estimating the INPARI 32 rice production and increase in income. The strategy is carried out through counseling, training, and rice planting demonstration plots that apply multilevel water system technology, and in-situ biomass (purunrat compost). The results of the activity show that 80–90% of farmers understand the application of this technology. Estimated grain yield of 5.62 t GKP/ha and a 300% increase in farmer income. Keywords: biomass, drainage, irrigation, wetlands, yields of padd